Alteration of the pilin adhesin of Pseudomonas aeruginosa PAO results in normal pilus biogenesis but a loss of adherence to human pneumocyte cells and decreased virulence in mice. - Farinha, M A (1994)
The disulfide loop domain of Pseudomonas aeruginosa PAO pilin was altered by insertion of a chloramphenicol acetyltransferase gene into the pilin gene so that the C-terminal nine amino acids were replaced with 11 new amino acids. The altered pilin gene was transferred into wild-type PAO by recombination, where it did not affect normal piliation as observed by transmission electron microscopy or change of sensitivity to f116, PO4, B9, and Pf1 pilus-specific bacteriophages. However, the binding to human pneumocyte A549 cells was markedly reduced when tested in an in vitro binding assay (2 to 6 bacteria bound per A549 cell for the mutant bacteria compared with 50 bacteria per A549 cell for the wild-type bacteria). Additionally, when susceptible A.BY/SnJ mice were challenged with wild-type P. aeruginosa PAO and with P. aeruginosa PAO-MP (altered pilin gene), a 50% lethal dose of 3 x 10(6) bacteria per mouse was observed for PAO-MP compared with 7 x 10(4) bacteria per mouse for PAO. Approximately 90 of the adherence capability of P. aeruginosa PAO is seemingly attributable to the C-terminal disulfide loop adherence domain of pili. The pilus adherence function contributes significantly to the virulence of P. aeruginosa PAO in the A.BY/SnJ mouse infection model.